2011
DOI: 10.3171/2011.4.spine10543
|View full text |Cite
|
Sign up to set email alerts
|

Blood supply and vascular reactivity of the spinal cord under normal and pathological conditions

Abstract: The authors present a review of spinal cord blood supply, discussing the anatomy of the vascular system and physiological aspects of blood flow regulation in normal and injured spinal cords. Unique anatomical functional properties of vessels and blood supply determine the susceptibility of the spinal cord to damage, especially ischemia. Spinal cord injury (SCI), for example, complicating thoracoabdominal aortic aneurysm repair is associated with ischemic trauma. The rate of this devastating complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
136
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(145 citation statements)
references
References 94 publications
(136 reference statements)
5
136
0
4
Order By: Relevance
“…The effect of systemic hypotension on outcome in acute SCI has been extensively evaluated in experimental studies and human medicine 21, 26. As a consequence of the loss of autoregulation that occurs during acute secondary SCI, spinal cord blood flow becomes directly vulnerable to fluctuations in MABP and intrathecal pressure 17, 46. A recent study in dogs undergoing ventral slot surgery for cervical IVDE found perioperative hypotension to be associated with major adverse events, including neurological deterioration 30.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of systemic hypotension on outcome in acute SCI has been extensively evaluated in experimental studies and human medicine 21, 26. As a consequence of the loss of autoregulation that occurs during acute secondary SCI, spinal cord blood flow becomes directly vulnerable to fluctuations in MABP and intrathecal pressure 17, 46. A recent study in dogs undergoing ventral slot surgery for cervical IVDE found perioperative hypotension to be associated with major adverse events, including neurological deterioration 30.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been recognized in the experimental setting that perfusion of the spinal cord is highly associated with outcome 16, 17, 18. Recent human and veterinary studies have furthered our understanding of the role of spinal cord perfusion and hemodynamic changes, as well as the benefits of taking appropriate measures to maintain optimal spinal cord blood flow 19, 20, 21, 22, 23.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is consistent with the high degree of variability in spinal vasculature more generally. In humans, the number of anterior and posterior radicular arteries was reported as varying between 2 to 17 and 11 to 25, respectively 37 and the variability of the venous system is reportedly higher than the arterial side. 28 The Dorsal Spinal Vein Serves as a Bidirectional Drain for the Mouse Spinal Cord and May Have a Role In Neurovascular Coupling Unlike veins in the periphery, the CNS (central nervous system) venous system does not contain one-way valves.…”
Section: The Mouse Dorsal Spinal Cord Vasculature Is Topologically Stmentioning
confidence: 99%
“…Secondary injury after primary spinal cord damage plays an important role in the final outcome. Pathological vascular changes and the subsequent events are crucial for the development of secondary injury [2][3][4] . Destruction of the blood-spinal cord barrier leads to massive leakage of blood components, initiating inflammation and gliosis [5] .…”
Section: Introductionmentioning
confidence: 99%